AWARENESS OF MEDICINAL APPLICATIONS OF RICE BRAN OIL AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
In the process of polishing rice , a specific vegetable oil high in antioxidant is generated first from outermost surface of rice designated Rice Bran Oil (RBO).a Experiments across the world have verified the anti lipidemic activity owing to the presence of special nutritional supplement in this oil recognized as oryzanol or tocotrienols. Raw rice bran product is usually made up of glycerides phospho and glycolipids as well as free fatty acids.The purpose of this survey was for assessing the awareness of medicinal applications of Rice bran oil among dental students.A cross sectional study was performed with a self-administered questionnaire with 10 queries circulated among 100 dental students. The questionnaire assessed the awareness about Rice bran oil therapy in medical applications ,their anti lipedemic properties, anti oxidant applications, harmone regulatin applications and immune enhancement activity.The responses were recorded and analysed.94% of the respondents were not aware of medicinal applications of Rice bran oiltherapy. 87% were not aware of anti lipedemic properties of Rice bran oiltherapy. 85% were not aware of anti oxidant properties of Rice bran oiltherapy.84% were not aware of armone regulation properties of Rice bran oiltherapy. 89% were not aware of immune enhancements properties of Rice bran oiltherapy.The awareness about the use of Rice bran oil therapy in medical applications is low among dental students.Increased awareness programs and sensitization and continuing dental education programs along with greater importance to the curricular modifications can further enhance knowledge and awareness about Rice bran oil therapy.